O roli języka w kształtowaniu tożsamości młodego pokolenia - Bańczyk, Emilia (Postscriptum Polonistyczne, 2020)
The author addresses the constantly relevant problem of the relationship between language and identity, gaining a new dimension in the context of transformations related to civilisation, globalisation and glocalisation. The research concerned students’ awareness of the role they believed language to play in the shaping of identity. For this purpose, surveys were conducted among 66 students of humanities. The paper fits in the field of ethnolinguistics and sociolinguistics.